Design and implementation of an automatic coin sorting and counting machine - Goh, Chin Guan (2015)
In this modern year, we can see that many automatic devices like drinking machine, washing machine, arcade game machine, massage chair and other coin operated machine using the automatic coin device to act as the coin counter and sorter. But, most of the coin counting machine in Malaysia is incapable to differentiate between the old and new Malaysian Coins accurately. The systems of the machine that are available in the market are not good enough because sometimes it makes mistake when detect the value of coin and cause the error calculation in the result. In this project, a coin operated machine which can differentiate old and new Malaysia coin accurately and automatically.is implemented. An automatic coin counting and sorting machine prototype is developed by using ARDUINO as the main controller. This work included design the simple display panel to show total quantity of each coin and total amount of coin value as the Crystal Display (LCD) has been implemented to display the result. The coin acceptor has been used as it acts as coin selector to determines the denomination of coin and forbid any invalid or unwanted coins. The coin sorting system is designed by using servo motor and the stepper motor to hold and distributes coin to the corresponding slot. Through the project, this integrated design has high performance for coin counting and sorting in terms of user-friendly, accuracy, and attractiveness.